THE ROLES OF BASIC INFRASTRUCTURE ON POVERTY ALLEVIATION IN INDONESIA - Nugroho, Sidiq Suryo (Badan kebijakan Fiskal, 2015)
The effect of infrastructure on poverty has been studied many times by researchers, but investigation about the transmission channel of infrastructure's effect on poverty needed more investigation due to more specific policy compiling. The aim of this present study is to investigate the role of basic infrastructure to fight the poverty by depicting the relationship of lenght of road, electricity transmission, clean water distribution, number of health care center, and number of school in particular areas with the poverty rate in Indonesia. This present study uses simple regression method, using panel data from 26 province level for year 2000-2008 in Indonesia. The result of this study reveals that road, electricity transmission, number of health care center, and number of school have an impact on poverty rate through economic growth which is proxied by human development index (HDI), in the other words the relationship between infrastructure and poverty is indirect relationship. Thus, if the Indonesian government is serious about reducing poverty, then the policy should give more emphasis on the poor and provide them with those basic infrastructures; and also have to improve the accessibility of the infrastructures for the poor people although its effect is indirectly.